102 Assessment of Work-Related Musculoskeletal Pain in Urologic Microsurgeons. Issue 1 (1st April 2022) - Schneider, D; Loeb, C; Nguyen, J; Coward, RM; Jenkins, L; Yafi, F
ABSTRACT: Introduction: Work-related musculoskeletal disorders (MSDs) are a broad category of potentially preventable conditions causing pain in or injury of the muscles, tendons, nerves, and bones that can be directly attributed to an occupation. Practicing surgeons are at high risk for MSDs due to forced neck flexion, awkward posture, and repetitive hand and arm movements. Urologists face unique ergonomic considerations, including those of laparoscopy, endoscopy, and microsurgery, compared to the general proceduralist population. Studies have shown the prevalence of musculoskeletal pain to be 45-62% in urologists. However, urologic microsurgeons have not to date been studied as a unique subgroup. Objective: We sought to evaluate the prevalence and risk factors of MSDs in urologic microsurgeons. Methods: An anonymous online survey was distributed to approximately 6, 000 urologists via email from a curated email database which included specialty society members. This survey included questions on demographics, operative time, exercise frequency and type, ergonomic interventions, and musculoskeletal symptoms. Symptoms were assessed using a de novo, modified Nordic Musculoskeletal Questionnaire (NMQ). Musculoskeletal trouble was defined in the survey as aches, pains, discomfort, or numbness in accordance with the NMQ. Results: A total of 50 responses were collected, proportional to the relatively small number of urologists performing these surgeries. The average age of respondents was 48.5 years, BMI was 26.4, and years in practice was 15.7. 29 (58%) completed a formal fellowship in andrology, male infertility, or microsurgery. The average number of operative days per week was 1.6 and the average number of microsurgical cases per month was 7.2. A total of 42 (84%) respondents reported musculoskeletal trouble in the past 12 months; 30 (60%) reported trouble in the past week; and 8 (16%) were forced to miss work due to their MSD in the past 12 months. Neck symptoms were most common (52%), followed by low back (50%) and shoulders (44%). Of those with symptoms in the past year, 24 (57%) respondents were prompted to seek professional medical help and 29 (69%) respondents were prompted to use medication. Furthermore, 25 (60%) respondents believed that their MSDs were a result of their occupation. 96% of respondents exercised, with the median respondent exercising three days a week for one hour each day. There was no association between hours of exercise and prevalence of MSDs. Similarly, there were no associations between operative volume, years in practice, or fellowship status with musculoskeletal symptoms. Of surgeons who sit to operate, only 40% experienced weekly symptoms, compared to 73% of surgeons who stand (p=0.02). This was most pronounced with low back pain, as 5% of surgeons who sit experienced weekly low back symptoms compared to 30% of those who stand (p=0.04). Conclusions: Work-related MSDs are highly prevalent in urologic microsurgeons, with 83% of surveyed surgeons experiencing musculoskeletal symptoms in the past year. Operating while seated was associated with a significantly lower incidence of MSDs compared to standing. Negative ergonomics of standing such as leaning or hunching with a non-ergonomic operative microscope likely plays a major role in the development of persistent MSDs in urologic microsurgeons. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: FY: Coloplast (consultant), Cynosure (consultant) LJ: Hims (consultant)